A210 CORRELATION OF ADENOMA PER CASE WITH ADENOMA DETECTION RATE FOR CREDENTIALED SCREENING COLONOSCOPISTS IN THE NOVA SCOTIA COLON CANCER PREVENTION PROGRAM. (15th March 2019) - Miles, M; Kilfoil, E; Walsh, G; MacIntosh, D
Abstract: Background: Quality indicators are used to evaluate endoscopist performance in colon cancer screening programs. Adenoma detection rate (ADR) is currently the most commonly used quality indicator. However, ADR has potential limitations prompting other quality indicators to be proposed. Adenoma per case (APC) appears to correlate with ADR and may better differentiate endoscopist performance. However, the relationship between APC and ADR is not fully established and the ideal target for APC remains unknown. Aims: The objectives of the study are to (1) determine the APC; (2) investigate the relationship between ADR and APC; and (3) explore target APC based on ADR for all screening endoscopists in the Nova Scotia colon cancer program as a means of quality assurance. Methods: This was a retrospective cross sectional review of a prospectively updated colonoscopy database at Dalhousie University. The study population was asymptomatic, average risk adults age 50–74 who had a screening colonoscopy after a positive fecal immunochemical test (FIT) from 2016–2017 as part of the Nova Scotia colon cancer screening program. Adenoma detection rate (ADR) was defined as the number of colonoscopies in which one or more adenomas was removed divided by the total number of colonoscopies performed. The number of adenomas per case (APC) was determined by dividing the total number of adenomas removed by the total number of colonoscopies performed. Pearson correlation coefficients were used to evaluate the relationship between and ADR-APC. Results: A total of 8379 colonoscopies were performed by 42 endoscopists on FIT positive patients over the study period. The mean number of colonoscopies per endoscopist was 200 (range 51–615). The mean APC for all endoscopists, those with ADR ≥ 50% and those with ≥ 60% are shown in Table 1. There was a significant positive correlation between ADR and APC (R=0.88; P<0.001). Conclusions: In the Nova Scotia Colon Cancer Prevention Program, there is a significant positive correlation between ADR and APC for screening endoscopists. A mean APC of 1.4 may be a useful target for endoscopists screening FIT positive patients. Funding Agencies: None